Vocational Training Models Based on Production and Business Activities to Develop Human Resources of Ethnic Minorities in the Northwest Provinces - Dong Thi Hong; Le Huong Giang (Sean Institute, 2022)
In the past few years, human resources in ethnic minority areas in the Northwest have tended to increase, but there has been a shift in the structure of human resources in this region by gender, increasing the proportion of male human resources and decreasing for women. Rural socio-economic development in general and the northwest mountainous region, in particular, requires many overall solutions including shifting labor structure from unskilled to skilled labor to increase labor value, thereby increasing labor productivity, meeting the requirements of industrialization, modernization of rural and mountainous areas. For the northwest ethnic minorities, agricultural production is the main economic activity. In addition, they also raise livestock, do some crafts, and carry out various forms of appropriation of available natural resources in the forests around the area of residence. Northwest ethnic minority communities and households have their unique products and business ideas, so vocational training for ethnic minority workers needs to be associated with these ideas to increase efficiency. For instance, using a vocational training model need to be based on the idea of promoting traditional professions, tourism development as well as agricultural development.